Development of virtual reliability methodology for area-array devices used in implantable and automotive applications - Sitaraman, S.K.; Raghunathan, R.; Hanna, C.E. (IEEE transactions on components and packaging technologies, 2000)
The number of thermal cycles, the temperature range, and the time of dwell used for qualifying a microelectronic package should be based on the type of application the package is intended for. However, in the absence of specific guidelines, the industrial practice is to subject the devices to military-standard qualification tests without adequate consideration for the application the devices are intended for. This work aims at developing temperature cycling guidelines for packages used in implantable medical devices and automotive applications taking into consideration the thermal history associated with the field conditions. Numerical models have been developed that take the time- and temperature-dependent behavior of the solder joints and the viscoelastic behavior of the underfill besides the temperature-dependent orthotropic properties of the substrate for a flip-chip on board (FCOB) assembly and a flip chip chip-scale package (FCCSP) on organic board assembly. The models account for solder reflow process, underfill cure process, and burn-in testing of the devices. Qualification temperature cycling guidelines have been developed for implantable devices based on the information collected in terms of shipping, EM sterilization, and implantation temperature profiles, and for the automotive devices based on the representative field conditions.